The Implementation of Constructivism Learning in Islamic Religious Subject At Senior High School Plus Bina Insani - Oktavita Sari (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
Constructivism approach in teaching and learning is based on a synthesis of several research in cognitive psychology and social psychology, as well as techniques of operant conditioning theory in behavioral psychology. The basic premise is that individuals must actively "build" their knowledge and skills (Brunner, 1990) from information obtained in the process of building a learning framework from the environment outside. Teachers will not be able to give all knowledge to their students. Students must construct knowledge in their own minds. The essence of constructivism theory is 'ideas'. Students must find and transform complex information into other situations. With that basis, teaching and learning process must be designed into a process of 'constructing' rather than 'receiving' knowledge